Tobacco Use Among Reproductive Age Women in Ethiopia: Evidence from the National Health Survey - Abdeta T; Hunduma G (Dove Medical Press, 2021)
Tilahun Abdeta, Gari Hunduma Department of Psychiatry, School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, Harar, EthiopiaCorrespondence: Tilahun AbdetaDepartment of Psychiatry, School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, PO Box 235, Harar, EthiopiaTel +251917649714Fax +251256668081Email tilahunabdeta@gmail.comPurpose: To assess the prevalence and determinants of current tobacco use among reproductive-age women in Ethiopia.Methods: A cross-sectional study was conducted by utilizing secondary data taken from the Ethiopian Demographic Health Survey of 2016. Descriptive statistics and logistic regressions were used to analyze the data. The odds ratio with a 95% confidence interval was considered to interpret associations and a significant association was stated at a p-value < 0.05.Results: The overall magnitude of current tobacco use was 1.4% (n= 217). Majority of them 59.91% (n= 130) smoke cigarettes and followed by smoking gaya 43.32% (n= 94). Higher prevalence was found among participants from Gambella 44.24% (n= 96), Benishangul.59% (n= 36) and afar regions 13.36% (n= 29). Age group of 25– 34 years [AOR = 2.78; 95% CI: 1.69, 4.57)], age group of ≥ 35 years [AOR = 4.24; 95% CI: 2.54, 7.07)], followers of protestant religion [AOR = 2.36; 95% CI: 4.17, 9.42], Islamic religion [AOR = 3.92; 95% CI: 2.16, 7.11], and traditional religion [AOR = 16.23; 95% CI: 8.33, 31.61], being in poorest wealth index [AOR = 15.78; 95% CI: 7.38, 33.70], poorer wealth index [AOR = 5.85; 95% CI: 2.64, 12.97], middle wealth index [AOR = 3.61; 95% CI: 1.57, 8.29], and richer wealth index [AOR = 2.48; 95% CI: 1.10, 5.85], who were never in union [AOR = 0.31; 95% CI: 0.14, 0.67], ever drinking alcohol [AOR = 5.44; 95% CI: 3.71, 7.95] and ever chewing khat [AOR = 7.59; 95% CI: 4.99, 11.55] were factors associated with current tobacco use.Conclusion: Women used tobacco in different forms, and its distribution varies across Ethiopian regional states. The concerned body needs to give attention to the identified associated factors and regions with higher tobacco use.Keywords: tobacco use, reproductive age women, Ethiopia